2008
DOI: 10.1007/s12024-008-9029-9
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem serum nitrogen compounds and C-reactive protein levels with special regard to investigation of fatal hyperthermia

Abstract: The present study analyzed serum levels of urea nitrogen (UN), creatinine (Cr), and C-reactive protein (CRP), which are very stable during the early postmortem period, for investigation of the cause of death with special regard to hyperthermia (heat stroke) in serial medico-legal autopsy cases (n = 429), excluding fatal injury, intoxication, and fire fatality. In this series, mechanical asphyxiation, drowning, and sudden cardiac death cases (n = 56, n = 43, and n = 212, respectively) usually showed low levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 32 publications
0
28
0
2
Order By: Relevance
“…The authors concluded that elevated serum CRP levels in cases of chronic renal failure may be related to the characteristics of diseases and/or infectious complications. For pneumonia, a markedly high serum CRP level may indicate the severity of infection, whereas a low CRP value in some infantile and elderly cases of pneumonia may be ascribed to an agedependent low inflammatory response [15].…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that elevated serum CRP levels in cases of chronic renal failure may be related to the characteristics of diseases and/or infectious complications. For pneumonia, a markedly high serum CRP level may indicate the severity of infection, whereas a low CRP value in some infantile and elderly cases of pneumonia may be ascribed to an agedependent low inflammatory response [15].…”
Section: Discussionmentioning
confidence: 99%
“…Moderately elevated CRP levels CRP, urea nitrogen, and creatinine Maeda et al [76] Postmortem serum Increased urea nitrogen, creatinine, and CRP levels CRP and neopterin Ishikawa et al [77] Postmortem serum from different sampling sites…”
Section: Discussionmentioning
confidence: 99%
“…Cold exposure cases were classified as nonacute deaths and short survivors (survival time up to 6 h) and displayed moderately elevated CRP levels (between 1 and 10 mg/l) compared with the other groups. Maeda et al [76] analyzed urea nitrogen, creatinine, and CRP in postmortem serum from the peripheral external iliac vein (or right heart chamber when peripheral blood was not available) in 429 medicolegal autopsy cases. They observed that the hypothermia fatalities had concomitant, significant elevations in the postmortem serum levels of urea nitrogen (>50 mg/dl), creatinine (>2 mg/dl), and CRP (>2 mg/ dl).…”
Section: C-reactive Protein and Neopterinmentioning
confidence: 99%
“…The results have showed that both markers, particularly CRP, can be used in forensic routine similar to clinical practice [78][79][80][81][82].…”
Section: Acute-phase Proteins and Cytokinesmentioning
confidence: 95%
“…Maeda et al [81] analysed urea nitrogen, creatinine, and CRP postmortem serum levels in 429 medico-legal autopsy cases and found that the combined use of these three markers could be useful for postmortem investigations of death due to hyperthermia, especially in the absence of pathological and toxicological evidence.…”
Section: Acute-phase Proteins and Cytokinesmentioning
confidence: 99%